The Effect of Designed Exercise Program on Fatigue in Women with Breast Cancer Receiving Chemotherapy - M Aghabarari (Iranian Journal of Public Health, 2008)
Background: Fatigue identified as the most prevalent, disturbing and disabling symptom that has profound impact on quality of life in patients with breast cancer receiving chemotherapy. In these patients, unnecessary bed rest and prolonged sedentariness can potentially contribute significantly to the development of fatigue, so this study was carried out to investigate and determine the effect of designed exercise program on fatigue in women with breast cancer receiving chemotherapy.